Quantification of silicon of foliage of guadua angustifolia From the Quindío (Revista de Investigaciones Universidad del Quindío, 2009)
A study about silica quantification in the bamboo foliage of Guadua angustifolia is presented. Through gravimetric techniques, it was found that silica percentage at the “Sendero Cedro Rosado” was 2.59% in dry weight basis (in ash), while the sample from the Natural Reserve “La Montaña del Ocaso” had a concentration of 1.70%. Through SEM and advanced fluorescent microscopy, it was found that Silica is deposited in the vascular bundles of the leaves and in lesser proportion within large cells.  Due to the diminishing of the density of the silica cells from the center toward the edges and apexes, we concluded that the presence of Silica in the bamboo foliage of Guadua angustifolia has functions of tissue mechanic stability.
Keywords: Guadua angustifolia; Poaceae; leaf; Silica quantification; Quindío; SEM; gravimetric techniques; fluorescent microscopy